(untitled) (Journal of Atomic and Molecular Sciences, 2014)
We investigate the structure of an Aharonov-Bohm interferometer with a quantum dot coupling to left and right electrodes. By employing cluster expansions, the equations of motion of Green's functions are transformed into the corresponding equation of motion of connected Green's functions, which provides a truncation scheme. With this method under the Lacroix's truncation approximation, we show that Fano resonance causes a decoherence of the Kondo singlet.